Selected aspects of narration in the integrated care of patients diagnosed with schizophrenia - Zurzycka, Patrycja; Wojtas, Katarzyna (Nursing Problems / Problemy Pielęgniarstwa, 2023)
Narrative has found application in medicine and the art of healing. Its particular importance can be shown in the integrated care of patients with mental disorders, practiced by both physicians and nurses. The experience of mental illness resulting in a change of the patient’s lifestyle builds an extremely rich human story, heard in the patient’s narrative, which allows the patient to be perceived holistically. The resulting respect for the patients’ individuality and subjectivity in the narrative, emphasizing their functioning in various dimensions, showing empathy is essential in caring for people who, due to psychopathological symptoms, are unable to interpret and perceive reality on their own, express emotions, or take care of their basic needs. The aim of this paper is to present selected narrative issues in the integrated nursing care of a patient with diagnosed schizophrenia.